Hepatitis C Treatment Regimens Are Cost-Effective: But Compared With What?. (November 2017) - Mattingly, T. Joseph; Slejko, Julia F.; Mullins, C. Daniel
Background: Numerous economic models have been published evaluating treatment of chronic hepatitis C virus (HCV) infection, but none provide a comprehensive comparison among new antiviral agents.Objective: Evaluate the cost-effectiveness of all recommended therapies for treatment of genotypes 1 and 4 chronic HCV.Methods: Using data from clinical trials, observational analyses, and drug pricing databases, Markov decision models were developed for HCV genotypes 1 and 4 to compare all recommended drugs from the perspective of the third-party payer over a 5-, 10-, and 50-year time horizon. A probabilistic sensitivity analysis (PSA) was conducted by assigning distributions for clinical cure, age entering the model, costs for each health state, and quality-adjusted life years (QALYs) for each health state in a Monte Carlo simulation of 10 000 repetitions of the model.Results: In the lifetime model for genotype 1, effects ranged from 18.08 to 18.40 QALYs and total costs ranged from $88 107 to $184 636. The lifetime model of genotype 4 treatments had a range of effects from 18.23 to 18.43 QALYs and total costs ranging from $87 063 to $127 637. Grazoprevir/elbasvir was the optimal strategy followed by velpatasvir/sofosbuvir as the second-best strategy in most simulations for both genotypes 1 and 4, with drug costs and efficacy of grazoprevir/elbasvir as the primary model drivers.Conclusions: Grazoprevir/elbasvir was cost-effective compared with all strategies for genotypes 1 and 4. Effects for all strategies were similar with cost of drug in the initial year driving the results.